LEADERSHIP CHALLENGES IN CONFLICT MANAGEMENT IN ORGANIZATIONS - Minov, Nina; Marič, Miha (International Journal of Economic Practice and Policy, 2024)
Conflicts are part of our everyday lives, and they occur both in private and work environment. In every organization, we face conflicts. In order to enable the organization to function better, it is important to manage conflicts correctly. The purpose of the research is to check what types of conflict management are used by employees in the organization and whether and how managers manage conflicts. The results show that a culture of avoidance dominates the organization in question, so we suggest that both employees and managers learn how to properly manage conflicts, which would lead to a better organizational culture in the long run.